Children around the world - Montanari, Donata (Toronto, ON ; Tonawanda, NY : Kids Can Press, 2001)
Delves into the culture, language, food, clothing, schooling, and daily life of twelve children around the world.
Translated from Italian.
Keywords: Children -- Social life and customs -- Juvenile literature; Manners and customs -- Juvenile literature; Enfants -- Mœurs et coutumes -- Ouvrages pour la jeunesse; Moeurs et coutumes -- Ouvrages pour la jeunesse; Children -- Social life and customs; Manners and customs; Juvenile works